Formulasi Sediaan Body Scrub Pencerah Kulit Dari Serbuk Kopi Robusta (Coffea Robusta L) dan Lidah Buaya (Aloe Vera) - Lidyawati, Lidyawati; Mardiana, Rosa; Pratiwi, Silvia Putri (Journal of Pharmaceutical and Health Research, 2025)
Body scrub is one form of pharmaceutical preparation that functions to clean the skin from dirt, dead skin cells, dust, and oil with the help of scrub particles that act as abrasives. Currently, the use of natural body scrubs is more popular because of the minimal risks and side effects. Robusta coffee beans and aloe vera extract contain flavonoid compounds that function as free radical scavengers. This study aims to determine whether robusta coffee beans (Coffea Robusta) and aloe vera extract (Aloe vera) can be used as a body scrub preparation to ward off free radicals, and to evaluate their physical stability through organoleptic testing, pH testing, homogeneity, accompanied by irritation testing. This study used an experimental method in the laboratory. The body scrub formulation was developed in three variations of the proportion of coffee extract and powder, namely F0 (0%), F1 (4.6%), and F2 (6.13%). Evaluation of the body scrub preparation includes organoleptic testing, homogeneity testing, pH testing, and skin irritation testing. The results showed that robusta coffee beans and aloe vera extract can be formulated into a body scrub preparation. The results of the pH test show that the pH of the body scrub is 6, according to the pH of the skin, so it is safe when applied to the skin. The results of the volunteer skin irritation test are also safe, having no irritating effect on the skin.